Transforming healthcare with DevOps : a practical guide on how to embrace the complexity of healthcare, along with technology - Mulder, Jeroen; Mulder, Henry (Packt Publishing, 2022)
Leverage modern technologies and agile methodologies such as DevOps and microenterprises to deliver sustainable healthcare solutions. About This Audiobook Distinguish the pace and time of change to achieve sustainable healthcare Apply shared mental models for common understanding of healthcare challenges and how to overcome them Apply and integrate new technology to accelerate the digital transformation of healthcare In Detail Healthcare today faces a multitude of challenges, which can be summed up as the barriers architects and consultants face in transforming the healthcare system into a more sustainable one. This book helps you to guide that transformation step by step. You'll begin by understanding the need for this transformation, exploring related challenges, the possibilities of technology, and how human factors can be involved in digital transformation. The book will enable you to overcome inhibitions and plan various transformation steps using the Transformation into Sustainable Healthcare (TiSH) model and DevOps4Care. Next, you'll use the observe, orient, decide, and act (OODA) loop as an iterative approach to address all stakeholders and adapt swiftly when situations change. Further, you'll be able to build shared platforms that enable interaction between various stakeholders, including the technology-enabled care service teams. The final chapters will help you execute the transformation to sustainable healthcare using the knowledge you've gained while getting familiar with common pitfalls and learning how to avoid or mitigate them. By the end of this DevOps book, you will have an overview of the challenges, opportunities, and directions of solutions and be on your way toward starting the transformation into sustainable healthcare. Audience This book is written specifically for enterprise architects and management consultants dealing with transformation in healthcare. Professionals dealing with digital transformation of healthcare, including C-level executives such as chief medical information officers (CMIOs), CEOs, CIOs, and CFOs will also find this book interesting. Basic knowledge of IT systems and architecture will help you grasp the concepts easily.